2019
DOI: 10.1111/bdi.12831
|View full text |Cite
|
Sign up to set email alerts
|

An International Society of Bipolar Disorders task force report: Precursors and prodromes of bipolar disorder

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 138 publications
(263 reference statements)
3
50
3
Order By: Relevance
“…In addition to severity of depression, patients with moderate and severe psychiatric disturbance during UD had an approximately twofold higher risk for conversion to BD than patients with mild disturbance. Furthermore, as in earlier studies, 9 we found patients with recurrent (previously non-hospitalized) depression to beat higher risk of converting to BD than patients with a single episode. As in the study of the Danish group, females were at higher risk of conversion to BD than males.…”
Section: Predictors For Diagnostic Conversionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to severity of depression, patients with moderate and severe psychiatric disturbance during UD had an approximately twofold higher risk for conversion to BD than patients with mild disturbance. Furthermore, as in earlier studies, 9 we found patients with recurrent (previously non-hospitalized) depression to beat higher risk of converting to BD than patients with a single episode. As in the study of the Danish group, females were at higher risk of conversion to BD than males.…”
Section: Predictors For Diagnostic Conversionsupporting
confidence: 88%
“…6 Although early diagnosis and treatment of these disorders would significantly reduce their enormous burden, apparent phenomenological similarity in the prodromal phases and clinicians' limited ability to predict the development of psychopathology on the individual level often challenge recognition of the major psychiatric disorders in clinical practice. Depressive symptoms and syndromes are common at the initial stages of both BD [7][8][9] and psychotic disorders. 10,11 As BD and schizophrenia differ in their prognosis and treatment approaches, knowing how commonly patients initially diagnosed with UD will subsequently convert to BD and psychotic disorders, when the diagnostic conversion will commonly occur, and what factors predict the conversion are critical for identifying depressed patients at risk.…”
Section: Introductionmentioning
confidence: 99%
“…These staging models, based on the hypothesis of neuroprogression in mental disorders, establish a basis for therapeutic intervention strategies in the different illness stages, including the early ones [13]. Evidence suggests the existence of a period of subthreshold and nonspecific symptoms (prodrome) before the full manifestation of the illness [14]. The most replicated finding to date has been the presence of subthreshold manic symptoms prior to the first full-blown manic episode [15].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent task force report of the International Society of Bipolar Disorders potential precursors of BD in patients with and without positive family history from prospective and retrospective studies are described, and the need for early recognition with the assessment of the many risk factors emphasized 30 …”
Section: Introductionmentioning
confidence: 99%